A parametric model on thermal evaluation of building envelopes containing phase change material. (1st February 2023) - Zhang, Yuan; Jiang, Weixue; Song, Jinwei; Xu, Li; Li, Shengcai; Hu, Lantian
Highlights: A parametric method for thermal evaluation of PCM building envelopes is established. Featuring by its ease of use for people with no relevant knowledge background. With the benefits of being fast, economical, and index-oriented when used by professionals. It can be used for parameter optimization and configuration improvement. Abstract: Appropriate methods for introducing phase change materials (PCM) into building envelopes (including walls and roofs) and performance investigation methods are essential for the thermal application of buildings equipped with PCMs. However, most of the existing evaluation methods, including numerical simulations and physical tests, are expertise-required, along with economic and time costs. In this paper, a thermal performance database covering 2401 different configurations of PCM-filled building envelopes is developed and performance trends of the envelopes are summarized based on the calculation of a validated enthalpy mathematical model. Based on the values in the database, a new parametric model of two mathematical equations for evaluating the thermal index values of PCM-filled envelopes is proposed. The average relative error of the model was 7.7 % compared to the numerical results. With a thermal resistance of 1 m 2 ·K·W −1 or higher and an indoor-outdoor temperature difference of 5 °C or higher, the model is applicable to most PCM-outfitted envelopes under the thermal conditions throughout a year, and can be used not only for thermal index calculations, but also for parameter value optimization and configuration improvement. The purpose of this study is to provide an approach for fast evaluation by professionals, and offer a friendly tool for general architects and engineers for the thermal investigation and optimization of building envelopes containing PCM.